PARENTAL EDUCATION AND FAMILY-BASED DA’WAH IN ISLAMIC SECONDARY EDUCATION: A QUALITATIVE STUDY IN INDONESIA - Asma, Fery Rahmawan; Muhajir , Achmad; Saputra, Eddy (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
This study examines the role of parental education level in shaping students’ understanding of Islamic Religious Education (IRE) through family-based da’wah practices at As-Salam Senior High School, Bogor, Indonesia. Grounded in the perspective of religious socialization and parental involvement, this research explores how educational background influences parents’ capacity to support, guide, and transmit Islamic values to their children. A qualitative descriptive approach was employed, involving in-depth interviews with students, Islamic education teachers, and parents, supported by classroom observations and document analysis. Participants were selected using purposive sampling to represent diverse parental educational backgrounds. Data were analyzed using interactive thematic analysis through data reduction, data display, and conclusion drawing. The findings reveal that parents with higher educational backgrounds tend to provide more structured academic and spiritual support, including religious discussions, access to learning resources, and contextual explanations of Islamic teachings. Consequently, their children demonstrate deeper cognitive, affective, and practical understanding of IRE. In contrast, parents with lower educational levels mainly emphasize moral guidance and religious modeling through daily practices, such as prayer and Qur’anic recitation, but offer limited academic assistance. As a result, students’ understanding is often confined to ritual and normative dimensions. Furthermore, school environment, peer interaction, and students’ intrinsic motivation also contribute to variations in religious understanding. This study highlights that parental education functions as a key medium of family-based da’wah that strengthens students’ religious comprehension and character formation. The findings emphasize the importance of collaboration between schools and families in strengthening Islamic education, particularly in supporting parents with limited educational backgrounds. This research contributes to the discourse on Islamic education and da’wah by demonstrating the strategic role of family in transmitting religious values in contemporary Muslim societies.